Improvement of Cost Overrun Issues with Building Information Modeling (BIM): A Case Study of the Malaysian Construction Industry - Tan , Yu Han; Ahmad Latiffi, Aryani (Research in Management of Technology and Business, 2024)
The construction industry in developing nations faces challenges of cost overrun, negatively impacting the economy and industry reputation. BIM’s digital representation and integrated data enable efficient planning, design, and construction processes, leading to cost reduction, and enhanced production efficiency. Cost overrun is a global phenomenon, and BIM technology addresses project cost concerns by promoting stakeholder participation and minimizing building costs. The objectives of the study is to study the benefits of BIM that can improve cost overrun in the Malaysian construction industry. Besides that, to investigate the barriers that hinder the adoption of BIM related to cost overrun and ways to overcome the barriers that hinder the adoption of BIM related to cost overrun in the Malaysian Construction Industry. The research methodology included a qualitative approach using case studies of 5 BIM projects in Klang Valley. Primary data collected through semi-structured interviews with construction practitioners involved with the BIM projects, while secondary data gathered from online resources and books. Content analysis employed to analyze the data collected from the interviews. Case studies demonstrated BIM’s efficacy in mitigating conflicts, improving communication, and early detection of design faults, preventing cost overrun. Barriers to BIM adoption, such as high initial costs and resistance to technological change, highlighted the necessity for government support, extensive training, and mandatory BIM policies to foster widespread utilization in the construction industry. This study advocated for BIM to improve cost overrun in Malaysian construction industry, offering insights, overcoming barriers, and providing strategic recommendations for industry-wide adoption and improvement.